The Effect of Students' Interest and Motivation in Participating in Online Mathematics Learning on Mathematics Learning Outcomes for VII SMP Class - Ruslan Ruslan; Asdar Asdar; Sri Kurniati (PT Mattawang Mediatama Solution, 2022)
This study aims to determine the effect of students' interest and motivation in participating in online mathematics learning on mathematics learning outcomes for class VII SMP. In this study, the interest and motivation of students to take part in learning mathematics in the network is the independent variable, while the learning outcomes of mathematics are the dependent variable. The sampling technique in this study used a random sampling technique and the number of samples was 78 students of class VII. The data collection technique was using test and non-test instruments. The instruments used are (1) a questionnaire on student learning interest in the network (2) a questionnaire on student learning motivation in the network (3) a test of mathematics learning outcomes. The data analysis method used multiple linear regression. The results showed that (1) students' interest in learning was in the high category (2) students' learning motivation was in the high category (3) student learning outcomes tests on algebraic form material were in the low category (4) students' interest and motivation in online learning were networked. together have no effect on the learning outcomes of class VII on algebraic material.